The Role of E-commerce on Sales in Selected Countries - Yehorov, Yehor (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
E-commerce is an activity aimed at selling goods and services using information technology based on network interactions between the buyer and the seller. E-commerce tools allow consumers to organize trading in securities, transactions between legal entities, conduct activities on electronic exchanges, realize an order and payment for consumer goods, tourist and educational services, and pay utility bills. E-commerce is a parts of the economy, which includes all financial and trade transactions carried out with the help of computer networks, and business processes associated with the conduct of such transactions. It is known that in recent years an increasing number of transactions have been carried out remotely, using electronic devices. This is due to the fact that electronic payments are more convenient and faster than payment in cash. This thesis deals with e-commerce and its impacts on sales in developed countries. The secondary data used for this study is extracted from official statistical sources. It is found out that in the five leading countries in e-commerce, sales and e-commerce is positively and strongly correlating. The main essence of the research was to be competitive in the market companies should include e-commerce into their system together with retail trade and gradually move to an electronic business management system. The recommendations developed in this thesis consist of the fact that companies need to integrate their business with users of mobile devices as their use is growing.

ÖZ: E-ticaret, alıcı ve satıcı arasındaki ağ etkileşimlerine dayalı olarak bilgi teknolojisini kullanarak mal ve hizmet satmayı amaçlayan bir faaliyettir. E-ticaret araçları, tüketicilerin menkul kıymetler ticareti, tüzel kişiler arasındaki işlemler düzenlemeleri, elektronik değiş tokuş faaliyetleri yürütmeleri, tüketici malları, turistik ve eğitim hizmetleri için bir sipariş ve ödeme gerçekleştirmesi ve kamu hizmeti faturaları ödemelerine olanak tanır. E-ticaret, bilgisayar ağı yardımıyla gerçekleştirilen tüm finansal ve ticari işlemleri içeren bu ekonomi alanını ve bu tür işlemlerin yürütülmesiyle ilgili iş süreçlerini kapsar. Son yıllarda, elektronik cihazlar kullanılarak, giderek artan sayıda işlemin uzaktan gerçekleştirildiği bilinmektedir. Bunun nedeni, elektronik ödemelerin nakit ödeme yönteminden daha kolay ve daha hızlı olmasından kaynaklanmaktadır. Bu tez, e-ticaret ve gelişmiş ülkelerdeki satışlar üzerindeki etkilerini ele almaktadır.. Bu çalışmada kullanılan ikincil veriler, resmi istatistiki kaynaklardan çıkarılmıştır. E-ticarette öne çıkan beş ülkede satış ve e-ticaretin pozitif yönde ilişkili olduğu görülmektedir. Araştırmanın ana özü piyasada rekabet edebilmekti. Şirketler, e-ticaretlerini perakende ticaretle birlikte sistemlerine dahil etmeli ve yavaş yavaş bir elektronik ticaret yönetim sistemine geçmelidirler. Bu tezde geliştirilen öneriler, işletmelerin sayıları giderek arttıkça işletmelerin mobil cihaz kullanıcılarıyla entegrasyon yapması gerektiğini içermektedir.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2017. Supervisor: Assoc. Prof. Dr. Melek Şule Aker.
Keywords: Business Administration; E-Commerce; E-commerce; e-commerce sales; retail sales; electronic business